2018
DOI: 10.1136/bcr-2017-222940
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary alveolar proteinosis following cryptococcal meningitis: a possible cause?

Abstract: Autoimmune pulmonary alveolar proteinosis (PAP) is a rare interstitial lung disease characterised by the presence of granulocyte macrophage colony-stimulating factor (GM-CSF) autoantibodies. A man with no history of infection developed cryptococcal meningitis and a right parahilar cryptococcal mass. Antifungal treatment led to infection control, although there was presence of neurological sequelae. After 3 years, thoracic CT revealed bilateral ground glass opacities and a crazy paving pattern. Transparietal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Patient plasmas were shown to inhibit GM-CSF-induced STAT5 phosphorylation [28]. Demir et al [29 ▪ ] presented a 42-year-old male with C. gattii meningitis and anti-GM-CSF autoantibodies and in whom PAP developed 3 years later. Huynh et al [30] reported another unusual presentation of endobronchial lesions due to C. gattii in the presence of anti-GM-CSF autoantibodies although their inhibitory activity was not formally ascertained.…”
Section: Antibodies To Granulocyt Macrophage Colony-stimulating Factomentioning
confidence: 99%
“…Patient plasmas were shown to inhibit GM-CSF-induced STAT5 phosphorylation [28]. Demir et al [29 ▪ ] presented a 42-year-old male with C. gattii meningitis and anti-GM-CSF autoantibodies and in whom PAP developed 3 years later. Huynh et al [30] reported another unusual presentation of endobronchial lesions due to C. gattii in the presence of anti-GM-CSF autoantibodies although their inhibitory activity was not formally ascertained.…”
Section: Antibodies To Granulocyt Macrophage Colony-stimulating Factomentioning
confidence: 99%
“…Based on our literature search, thus far, there is only one case report from France that reported a case of confirmed autoimmune PAP preceded by Cryptococcus gattii meningitis with positive anti-GM-CSF antibody [19]. Two similar cases were reported from America with Cryptococcus neoformans.…”
Section: Discussionmentioning
confidence: 99%
“…Anti GM-CSF antibodies were positive in high titre. He was not offered any specific treatment and three years after the diagnosis of PAP patient remained asymptomatic with near complete resolution of radiological lesion and decrease in anti-GM-CSF antibody titre [19].…”
Section: Casementioning
confidence: 99%
“…Nowadays, reports of OIs in patients with confirmed anti-GM-CSF autoantibodies with or without PAP have been increasing. 8,15,18,[23][24][25][26][27][28][29][30] Since the first documented case of anti-GM-CSF autoantibodies associated with disseminated cryptococcosis, 15 a total of 27 cases have been reported in the literature (Table 1). The median age at the time of presentation was 41 years (range 20-73 years).…”
Section: A S E Discussion and Re Vie W Of The Liter Aturementioning
confidence: 99%